Wool characteristic of Priangan sheep and its crossbred - ono syamyono; I. Inounu; M. Yamin (Indonesian Center for Animal Research and Development (ICARD), 2003)
The aim of this research was to identify wool characteristic of Priangan sheep (G) and its crossbred with St. Croix (H) andM. Charolais (M). The parameters observed included yield, fiber length, fiber diameter, percentage of shrink during processing,yarn production, strength and elasticity of the yarn. Eighteen rams of Priangan, HMG and MHG crossbred were used.Completely Randomized Design with 6 replications and One Way analyses were used in data analysing, except for strength andyarn elasticity, 10 replication were used. The results show that breed had no significant effect (P>0.05) on yield, diameter of finefiber, and shrinking percentage during separation and carding process. In contrast, breed had significant effect on fiber length(P<0.01) and on coarse fiber diameter, the shrink, strength and yarn elasticity (P<0.05). In general, the wool of HMG and MHGcrossbred had better quality compared to Priangan sheep, although yarn production was higher in Priangan sheep.Key words: Wool, Priangan sheep, crossbred